MICU1-dependent mitochondrial calcium uptake regulates lung alveolar type 2 cell plasticity and lung regeneration - Mir Ali; Xiaoying Zhang; Ryan LaCanna; Dhanendra Tomar; John W. Elrod; Ying Tian (JCI Insight, 2022)
Lung alveolar type 2 (AT2) cells are progenitors for alveolar type 1 (AT1) cells. Although many factors regulate AT2 cell plasticity, the role of mitochondrial calcium (mCa2+) uptake in controlling AT2 cells remains unclear. We previously identified that the miR-302 family supports lung epithelial progenitor cell proliferation and less differentiated phenotypes during development. Here, we report that a sustained elevation of miR-302 in adult AT2 cells decreases AT2-to-AT1 cell differentiation during the Streptococcus pneumoniae–induced lung injury repair. We identified that miR-302 targets and represses the expression of mitochondrial Ca2+ uptake 1 (MICU1), which regulates mCa2+ uptake through the mCa2+ uniporter channel by acting as a gatekeeper at low cytosolic Ca2+ levels. Our results reveal a marked increase in MICU1 protein expression and decreased mCa2+ uptake during AT2-to-AT1 cell differentiation in the adult lung. Deletion of Micu1 in AT2 cells reduces AT2-to-AT1 cell differentiation during steady-state tissue maintenance and alveolar epithelial regeneration after bacterial pneumonia. These studies indicate that mCa2+ uptake is extensively modulated during AT2-to-AT1 cell differentiation and that MICU1-dependent mCa2+ uniporter channel gating is a prominent mechanism modulating AT2-to-AT1 cell differentiation.